The role of tour manager in assessing and planning travel opportunities in Covid-19 new normal era for the locals - Wahyuningputri, Rode Ayu; Hendra, Hendra; Nova Putra, Aditya; Levyta, Farah; Pantja Djati, Sundring (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2022)
Indonesia tourism should make a move if it has superior and quality tourism resources. The travel sector feels the impact of the pandemic Covid 19 but recovering in their efforts and continue to prioritize on tourism as its main business. Tour Manager must develop a new strategic tour plan by taking advantage of potential opportunities for local communities as their partners. This qualitative research uses descriptive approach in describing the research problems above and answer three research questions, that is: (1) How big the role of the Tour Manager in planning travel tours? (2) What are the steps in planning a travel tour? (3) What are the potential opportunities are the benefits that can be developed. Tour Manager as part of the Human Resources is competent in assessing the opportunities and potential of tourism planning strategies and the general benefits of tourism development for locals. Updated Standard Operating Procedures are made to be applied by Tour Managers. With an understanable SOP, occupation can be measured and traced what has been and has not been done.